INTERACTION ANALYSIS HULL AND PROPELLER AND IMPROVEMENT OF EFFICIENCY PROPELLER ON FISHING VESSELS - Jami'in, Mohammad Abu; Primanjaya, Abi (Department of Marine Engineering, Universitas Hang Tuah, 2024)
The determination of propeller and hull adjustment of both small and large fishing vessels is indeed very important, in general, fishing vessels at the port of Lamongan only use hereditary techniques. many weaknesses in the problem of synchronization between the hull, the main propulsion engine, and the propeller. therefore, after analysis, it can be concluded, that at the coastal port of Lamongan, an Ijon-Ijon type fishing boat, with a main size of 5-10 GT. In one ship using the Mitsubishi Fuso 120 ps 2 engine type, using 2 gearbox advance ratio 3.1 rated input speed 1000- 2500 r/min and rated trans capacity 0.039 kW/min with a total resistance value of 17.599 kn, wake fraction value 0.235, value thrust deduction 0.197 and using a propeller with type B-series B3-35 with a diameter of 1.54 with a KT value of 0.31, a value of 10KQ 0.37, a value of J 0.52 and an average efficiency value of 0.48. By changing the diameter propeller to 1.75 and changing the ratio gearbox with the same engine, a comparison can be made between the efficiency of the propeller previous and the efficiency after changing the diameter propeller with a KT value of 0.30, a value of 10KQ 0.345, a value of J 0.55 and average efficiency value 0.565.